Detection and allele identification of rice blast resistance gene, Pik, in Thai rice germplasm - Ariya-anandech, Kasirapat; Chaipanya, Chaivarakun; Teerasan, Wattanaporn; Kate-Ngam, Sureeporn; Jantasuriyarat, Chatchawan (Agriculture and Natural Resources, 2018)
The objectives of this study were to detect the rice blast resistance gene, Pik, in Thai rice germplasm and to identify their alleles. Rice blast resistance gene specific primers were designed and used to screen for the presence of the Pik resistance gene in 373 Thai rice varieties. The results showed that 29 out of the 373 Thai rice varieties contained the Pik gene. All 29 polymerase chain reaction (PCR) products were digested by the PstI restriction enzyme. PCR products from 25 rice varieties could be digested by the PstI enzyme, indicating that they contained the Pikp resistance group, which has a narrow disease spectrum. The PCR products from four rice varieties could not be digested by the PstI enzyme, suggesting that they contained the desirable Pikm resistance group, which has a broad disease spectrum. The nucleotide sequences of these four rice varieties in the Pikm resistance group revealed that the Khaw reng rice variety had the Pikm allele and the other three rice varieties had the Piks allele. Khaw reng can be used as an elite resistant donor in conventional and molecular breeding programs for blast disease resistance in Thailand.